Emerging Bodies The Performance of Worldmaking in Dance and Choreography - Klein, Gabriele; Noeth, Sandra (TanzScripte, 2011)
The concept of 'worldmaking' is based on the idea that 'the world' is not given, but rather produced through language, actions, ideas and perception. This collection of essays takes a closer look at various hybrid and disparate worlds related to dance and choreography. Coming from a broad range of different backgrounds and disciplines, the authors inquire into the ways of producing 'dance worlds': through artistic practice, discourse and media, choreographic form and dance material. The essays in this volume critically reflect the predominant topos of dance as something fleeting and ephemeral - an embodiment of the Other in modernity. Moreover, they demonstrate that there is more than just one universal 'world of dance', but rather a multitude of interrelated dance worlds with more emerging every day.